High Incidence of Atrial Fibrillation After Embolic Stroke of Undetermined Source in Posterior Cerebral Artery Territory. Issue 12 (29th November 2017) - Makimoto, Hisaki; Kurt, Muhammed; Gliem, Michael; Lee, John‐Ih; Schmidt, Jan; Müller, Patrick; Clasen, Lukas; Brinkmeyer, Christoph; Shin, Dong‐In; Jander, Sebastian; Kelm, Malte; Fürnkranz, Alexander
Abstract : Background: Subclinical atrial fibrillation is one possible cause of embolic stroke of undetermined source (ESUS). It remains to be elucidated if a specific infarction site has a predictive value for detecting subclinical atrial fibrillation. We aimed to investigate the predictive value of infarction site in patients with ESUS for the detection of atrial tachyarrhythmia (AT) using an insertable cardiac monitor. Methods and Results: Consecutive 146 patients (84 men; aged 62±12 years) underwent insertable cardiac monitor implantation after diagnosis of ESUS. The detection of AT >30 seconds was evaluated. The ESUS infarction sites were categorized into internal carotid artery and vertebral artery (VA) territories, with ophthalmic artery, anterior cerebral artery, and middle cerebral artery as internal carotid artery subterritories, and posterior cerebral artery and other vertebrobasilar arteries as VA subterritories. During a median follow‐up of 387 days, AT was detected in 33 patients (23%). Subclinical AT detection was significantly more frequent after VA territorial infarction opposed to internal carotid artery infarction (20/57 [35%] versus 13/89 [15%]; P =0.0039). Kaplan‐Meier analysis demonstrated a significantly higher AT detection rate after VA infarction (log‐rank, P =0.0076). Regression analysis revealed that VA territorial infarction, and particularly posterior cerebral artery area infarction, was an independent predictor of AT detection. Conclusions: Patients with ESUS in the posterior cerebral artery territory had a higher rate of subclinical AT detection than those with other infarct localizations. Our data suggest that the possible usefulness of ESUS site to identify candidates for direct oral anticoagulation should be confirmed in future research.